Analysis of the marketing channel of cayyye cayme in the village Lalemba lawa district, west muna district - Rista Astuti; Surni Surni; Samsul Alam Fyka (International Journal of Economics, Business and Innovation Research, 2023)
This research aims to determine the marketing channels for cayenne pepper, profits, margins, costs and marketing efficiency of cayenne pepper in Lalemba Village, Lawa District, West Muna Regency. The results of this research show that there is 1 marketing channel for cayenne pepper in Lalemba Village, Lawa District, West Muna Regency, namely: Farmers, Traders, Collectors Consumer.The marketing margin for the channel is IDR 10,000/Kg. Meanwhile, the profit from the marketing channel is IDR 6,953.4/Kg or the total profit for a month is IDR 1,043,010 Kg, this is because the marketing channel for cayenne pepper in Lalemba Village, Lawa District, West Muna Regency only has one marketing channel. The results of this analysis show that the percentage share of the price received by farmers (Farmer's Share) from the marketing of cayenne pepper in Lalemba Village, Lawa District, West Muna Regency is efficient, indicated by an FS value above 50%, namely FS = 84%.